A Comprehensive Presentation of the Turbulent Plane Jet Theory with Passive Scalar. (25th May 2017) - Violeau, D.
Abstract : We present a unified vision of the existing theoretical models for the turbulent plane jet, leading to new analytical profiles for scalar concentration and turbulent quantities, including a complete turbulent kinetic energy budget. Integrals of the budget terms are also computed. The present model is split into two variants. Both compare fairly well with referenced experimental data.